Diversification of brackishwater aquaculture in Indonesia: tilapia culture in Aceh - Michael A. Rimmer; Coco Kokarkin; . Hasanuddin; Bakhtiar Sah Putra; . Syafrizal; . Saripuddin; Imran Lapong (Syiah Kuala University, 2012)
Traditional brackishwater aquaculture in Indonesia focuses on production of shrimp and milkfish. However, since the 1990’s production of shrimp, particularly Penaeus monodon, has become problematic because ofthe prevalence of white-spot disease. Crop losses due to white-spot disease have limited production of P. monodon in traditional tambak throughout Indonesia. Because of this, many tambak have fallen into disuse, or their use islimited. In response, we are developing and trialling diversification options for tambak farmers in Aceh and South Sulawesi. Alternative production options that we are evaluating include Nile tilapia (ikan nila) and soft-shell crab(kepiting lunak) in Aceh, and Nile tilapia, swimming crab (rajungan) and rabbitfish (baronang) in South Sulawesi. In Aceh our main focus has been on Nile tilapia (Oreochromis niloticus) culture, either alone or co-cultured with milkfish (Chanos chanos). We have undertaken trials with farmers in Samalanga and Jangka (Kab. Bireuen) and Banda Mulia (Kab. Aceh Tamiang). Overall, our trials have shown that tilapia will grow and survive well at salinities below 20 ppt. Above 20 ppt, growth rate is reduced and the fish are prone to bacterial disease. At salinities above 20 ppt, milkfish (bandeng) perform better in ponds than tilapia. Our trials in Aceh have demonstrated that Nile tilapia can provideincome to farmers comparable with shrimp culture. Out of a total of 22 trials to date, 9 ponds (41%) have met or exceeded our reference profitability of IDR 1–5 million per hectare per crop. Fourteen ponds (64%) have been‘profitable’, i.e. have generated positive economic returns. This figure is similar to the profitability figure for traditional shrimp ponds (64–73%), indicating that Nile tilapia culture in brackishwater ponds provides economic returns similar to traditional shrimp culture. Based on these results, we recommend Nile tilapia culture to farmers whose ponds are 20 ppt. This provides a profitable production option for farmers in areas subject to low salinities, or during the rainy season when salinities are depressed. Because outbreaks of white-spot disease are particularly common and severe during the rainy season, Nile tilapia culture provides a viable option for income generation for Acehnese tambak farmers under conditions where shrimp culture is too risky